Value assessment of medicinal products by the Italian Medicines Agency (AIFA) and French National Authority for Health (HAS): Similarities and discrepancies - Xoxi, Entela; Di Bidino, Rossella; Leone, Serena; Aiello, Andrea; Prada, Mariangela (Frontiers in Medical Technology, 2022)
The evaluation of pharmaceutical innovation and therapeutic value is an increasingly complex exercise for which different approaches are adopted at the national level, despite the need for standardisation of processes and harmonisation of public health decisions. The objective of our analysis was to compare the approaches of the AIFA (Agenzia Italiana del Farmaco) and the HAS (Haute Autorité de Santé) in assessing the same medicinal products. In Italy, the 1525/2017 AIFA Deliberation introduces a transparent scheme for the evaluation of innovative status (innovative, conditional, not innovative) based on the therapeutic added value (TAV), therapeutic need, and quality of evidence. In contrast, in France, the HAS makes judgements using the effective clinical benefit (Service Médical Rendu) and improvement of effective clinical benefit (Amélioration du Service Médical Rendu, ASMR). This analysis focused on medicinal products evaluated both by the AIFA and by the HAS from July 2017 to September 2021. Similarities between AIFA and HAS evaluations were investigated in terms of the TAV, recognition of innovativeness, and the ASMR. Both total and partial agreements were considered relevant. Therefore, raw agreement, Cohen's kappa (weighted and unweighted), and Bangdiwala's B-statistic were estimated. A total of 102 medicinal products were included in this study. Out of these, 38 (37.2%) were orphan drugs, while 56 (54.9%) had a clinical indication for the treatment of cancer. The AIFA and HAS reached a higher level of agreement on the innovativeness status compared with the TAV. A moderate total agreement emerged in the recognition of innovativeness (k = 0.463, p-value ≤0.0001), and partial agreement was substantial (equal weight k = 0.547, squared k = 0.638), while a lack of agreement resulted in a comparison of the TAV according to the AIFA and the ASMR recognised by the HAS. Indeed, whereas the AIFA determined the TAV to be important, the HAS considered it to be moderate. In addition, whereas the AIFA identified a bias towards a moderate TAV, the HAS identified a bias towards a minor ASMR. A higher level of agreement was reached, both on the TAV and on innovative status, for less critical medical products (non-cancer-related, or non-orphan, or with a standard European Medicines Agency approval). These results underline the importance of implementing European procedures that are more broadly aligned in terms of value definition criteria.